2020
DOI: 10.24929/lensa.v10i1.98
|View full text |Cite
|
Sign up to set email alerts
|

Penyelenggaraan Pembelajaran Ipa Berbasis Pendekatan Stem Dalam Menyongsong Era Revolusi Industri 4.0

Abstract: Pendidikan berbasis revolusi industri 4.0 memerlukan alternatif solusi yang membuat lembaga pendidikan harus selalu memadukan metode inovatif untuk meningkatkan pengajaran dan pembelajaran. Tujuan dari penelitian ini adalah untuk menganalisis aspek-aspek penunjang pembelajaran IPA serta cara mengimplementasikannya dalam menyongsong era revolusi industri 4.0. Metode Penelitian ini mengunakan metode library research. Hasil penelitian ini adalah (1) aspek-aspek penunjang dalam pembelajaran IPA yang memenuhi tuntu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 17 publications
0
16
0
6
Order By: Relevance
“…Among the various teaching materials, interactive teaching materials containing audio, video, text, or graphics can be an alternative for students. (Grahito Wicaksono, 2020) revealed that teaching materials in the form of video tutorials regarding remote practicums could represent a teacher as a student mentor in implementing practical learning. In addition, video tutorials designed as interactive practicum guides are considered more effective during distance learning because students can access them anytime without being limited by time as using virtual meeting applications (Suryanda, 2020) Research from Anggreini A (2021) states that E-modules is the best alternative in developing teaching materials for distance learning, where there are learning objectives, materials, learning activities, exercises, quizzes, and feedback equipped with videos.…”
Section: Evaluation Of Science Practicum Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various teaching materials, interactive teaching materials containing audio, video, text, or graphics can be an alternative for students. (Grahito Wicaksono, 2020) revealed that teaching materials in the form of video tutorials regarding remote practicums could represent a teacher as a student mentor in implementing practical learning. In addition, video tutorials designed as interactive practicum guides are considered more effective during distance learning because students can access them anytime without being limited by time as using virtual meeting applications (Suryanda, 2020) Research from Anggreini A (2021) states that E-modules is the best alternative in developing teaching materials for distance learning, where there are learning objectives, materials, learning activities, exercises, quizzes, and feedback equipped with videos.…”
Section: Evaluation Of Science Practicum Resultsmentioning
confidence: 99%
“…(Edelson et al, 2021)The science learning process should emphasize providing direct experience to develop competence in exploring and understanding nature scientifically. Natural science learning is directed at inquiry and action to help students gain a more meaningful understanding of the natural surroundings (Subiantoro, 2014) Natural sciences is one of the subjects contained in the educational curriculum structure, which is intended to recognize, respond to, and appreciate science and technology and instill habits of thinking and behaving scientifically, critically, creatively and independently (Grahito Wicaksono, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Hakikat IPA sebagai produk ilmiah berisi kumpulan pengetahuan, IPA sebagai proses ilmiah mengacu pada cara menginvestigasi suatu masalah menggunakan keterampilan proses sains (metode ilmiah), IPA sebagai sikap ilmiah mengacu pada cara mengembangkan kemampuan berpikir, dan IPA sebagai aplikasi adalah penggunaan konsep-konsep abstrak yang dapat dimanifestasikan dalam bentuk-bentuk spesifik maupun teknologi (Chiappetta & Koballa, 2010). Pembelajaran IPA adalah proses yang dapat membantu siswa belajar lebih bermakna melalui keterampilan proses sehingga mereka dapat menguasai pengetahuan ilmiah dan hukum alam serta menerapkannya dalam konteks kehidupan nyata (Wicaksono, 2020). Selain itu, media komik ini dapat meningkatkan daya pikir visual siswa sekaligus sebagai media hiburan (Novianti & Syaichudin, 2015).…”
Section: Pendahuluanunclassified
“…Thus, the provision of knowledge without experience is not sufficient for developing metacognitive abilities. Educators' priority on their students' metacognitive abilities will influence students in creating new knowledge and applying it to new situations (Dirkes, 1988;Kusumaningrum, 2018;W., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of STEM is more relevant to apply to elementary schools, that is because interdisciplinary handling and integrated learning do not change drastically at that level of education (Davidi et al, 2021;Stohlmann, 2022;W., 2020). The basis for the implementation of STEM is direct learning or learning based on the experiences of students (Seage & Türegün, 2020;Toma & Greca, 2018).…”
Section: Introductionmentioning
confidence: 99%